PENGARUH KUALITAS LAYANAN, MARKETING RELATIONSHIP DAN HANDLING SWITCHING TERHADAP LOYALITAS NASABAH BRI KEDUNGADEM KABUPATEN BOJONEGORO - M. Arif Mukhlisin; Wasis Budiarto; Woro Utari (Prodi Magister Manajemen Universitas Wijaya Putra, 2018)
This study aims to determine and improve the quality of services, marketing relationships and switching handling of customers loyalty at Bank BRI Kedungadem Bojonegoro. In addition to test and handle changes in service quality, relationship and handling either partially or simultaneously to customer loyalty at Bank BRI Kedungadem Bojonegoro Regency. Sampling technique using accidental sampling is sampling is done by giving a questionnaire to the customers encountered at the time. In this study the number of samples obtained as much as 100 customers. The method used is descriptive statistics and type of this research is expalanatory research. The result of data analysis shows the variable of service quality, marketing reliability, handling switching to customer loyalty of Bank BRI Kedungadem Bojonegoro Regency in good condition. Quality of service, marketing relationships, handling of switching simultaneously significantly influence customer loyalty Bank BRI Kedungadem Bojonegoro regency. Service quality partially has a significantly influence on customer loyalty, while marketing relations and handling of switching is partially insignificant to customer loyalty at Bank BRI Kedungadem Bojonegoro Regency. Keywords : quality of services, marketing relationship, switching handling, customers loyalty